Development planning in India: the ideological dimension - Choudhary, Kameshwar (1998)
Development planning in India is around half-a-century old. It has developed its own culture with important ideological underpinnings. Generally, in evaluating development planning the focus is given on the gaps between the proclaimed goals and the actual achievements made under the five year plans. But this paper examines the ideological aspects of development planning as reflected in the internal inconsistencies found in the plan documents, particularly in the Eighth Plan, as well as their latent intent. It is shown here that planning in India has essentially followed the capitalist path of development from the very beginning. Capitalism was skilfully nurtured under the garb of developing `socialistic pattern of society' in the early plans. As the capitalist baby got grown up, the planners tore off the cloak and proclaimed openly the adoption of market-led economy with the launching of the Eighth Plan in the country. The capitalist class was made free to go for globalization and grow further. But the common people were left to fend for themselves in the invisible hands of the market. - Reproduced
Keywords: Development planning